Exploring the Issue of Alienation in Orwell’s Animal Farm through the Eyes of Marxism - S. Ali, Fares Mohammed; Ubale, Anand; Abdulla, Ali Fadhel Mohmmed (BIRCU, 2025)
Orwell included the issue of alienation in almost major of his writings particularly his famous book Animal Farm. The current research paper highlights the major argument of the Marxist approach which is alienation throughout Animal Farm. In this regard, the researcher focuses largely on the critical-analytical study of the idea of alienation based on the Marxist point of view. A deep exploration is paid to the analysis of all forms that are closely related to the concept of alienation concerning socio-political alienation, economic alienation, self-alienation, psychological alienation, and religious alienation. Based on the rereading of the whole incidents of the book, the present study investigates the major concept of Marxism namely alienation in the light of the Marxist perspective. It is seen that both ruling authority groups either the previous Manor Farm that is led by Mr. Jones or the latter the Animal Farm that is led by the Pigs, Old Major before revolution and Napoleon and Snowball after revolution practiced alienation on their subjects in order to dominate them.